End times : a brief guide to the end of the world, asteroids, supervolcanoes, rogue robots, and more - Walsh, Bryan (Hachette Books, 2019)
End Times is a compelling work of skilled reportage that peels back the layers of complexity around the unthinkable--and inevitable--end of humankind. From asteroids and artificial intelligence to volcanic supereruption to nuclear war, 15-year veteran science reporter and TIME editor Bryan Walsh provides a stunning panoramic view of the most catastrophic threats to the human race. In End Times, Walsh examines threats that emerge from nature and those of our own making: asteroids, supervolcanoes, nuclear war, climate change, disease pandemics, biotechnology, artificial intelligence, and extraterrestrial intelligence. Walsh details the true probability of these world-ending catastrophes, the impact on our lives were they to happen, and the best strategies for saving ourselves, all pulled from his rigorous and deeply thoughtful reporting and research. Walsh goes into the room with the men and women whose job it is to imagine the unimaginable. He includes interviews with those on the front lines of prevention, actively working to head off existential threats in biotechnology labs and government hubs. Guided by Walsh's evocative, page-turning prose, we follow scientific stars like the asteroid hunters at NASA and the disease detectives on the trail of the next killer virus. Walsh explores the danger of apocalypse in all forms. In the end, it will be the depth of our knowledge, the height of our imagination, and our sheer will to survive that will decide the future.